Biochemical and pharmacological characterization of the human lymphocyte antigen B-associated transcript 5 (BAT5/ABHD16A). - Juha R Savinainen (Public Library of Science (PLoS), 2014)
Background Human lymphocyte antigen B-associated transcript 5 (BAT5, also known as ABHD16A) is a poorly characterized 63 kDa protein belonging to the α/β-hydrolase domain (ABHD) containing family of metabolic serine hydrolases. Its natural substrates and biochemical properties are unknown. Methodology/principal findings Amino acid sequence comparison between seven mammalian BAT5 orthologs revealed that the overall primary structure was highly (≥95%) conserved. Activity-based protein profiling (ABPP) confirmed successful generation of catalytically active human (h) and mouse (m) BAT5 in HEK293 cells, enabling further biochemical characterization. A sensitive fluorescent glycerol assay reported hBAT5-mediated hydrolysis of medium-chain saturated (C14:0), long-chain unsaturated (C18:1, C18:2, C20:4) monoacylglycerols (MAGs) and 15-deoxy-Δ12,14-prostaglandin J2-2-glycerol ester (15d-PGJ2-G). In contrast, hBAT5 possessed only marginal diacylglycerol (DAG), triacylglycerol (TAG), or lysophospholipase activity. The best MAG substrates were 1-linoleylglycerol (1-LG) and 15d-PGJ2-G, both exhibiting low-micromolar Km values. BAT5 had a neutral pH optimum and showed preference for the 1(3)- vs. 2-isomers of MAGs C18:1, C18:2 and C20:4. Inhibitor profiling revealed that β-lactone-based lipase inhibitors were nanomolar inhibitors of hBAT5 activity (palmostatin B > tetrahydrolipstatin > ebelactone A). Moreover, the hormone-sensitive lipase inhibitor C7600 (5-methoxy-3-(4-phenoxyphenyl)-3H-[1], [3], [4]oxadiazol-2-one) was identified as a highly potent inhibitor (IC50 8.3 nM). Phenyl and benzyl substituted analogs of C7600 with increased BAT5 selectivity were synthesized and a preliminary SAR analysis was conducted to obtain initial insights into the active site dimensions. Conclusions/significance This study provides an initial characterization of BAT5 activity, unveiling the biochemical and pharmacological properties with in vitro substrate preferences and inhibitor profiles. Utilization of glycerolipid substrates and sensitivity to lipase inhibitors suggest that BAT5 is a genuine lipase with preference for long-chain unsaturated MAGs and could in this capacity regulate glycerolipid metabolism in vivo as well. This preliminary SAR data should pave the way towards increasingly potent and BAT5-selective inhibitors.